PENGARUH LIFESTYLE DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN TIKET PESAWAT GARUDA INDONESIA DI BANDAR UDARA INTERNASIONAL SOEKARNO HATTA - Devi Nurafni Putri Purnomo (CV. ADIBA AISHA AMIRA, 2024)
The impact of the era globalization means that people’s lifestyles are always changing along with developments in science, technology, and information. Lifestyle also influences the choice of brand image for a product or service to be used. Changes in lifestyle and the choice of brand image cannot be separated from consumer purchasing decisions, including in terms of choosing the airline used for travelling. The objective of this research is to determine the effect of lifestyle and brand image on the decision to purchase Garuda Indonesia Airline tickets at Soekarno Hatta International Airport and to find out how big this influence is. This research applied a quantitative approach using survey methods. The research was conducted from 01 August 2023 to 30 September 2023, located at Soekarno Hatta International Airport. The data collection technique used a survey method by distributing questionnaires. The data analysis techniques used T test, F test, multiple linear regression analysis, and test. The results of this research show that there is an effect of lifestyle on purchasing decisions with a significance value of 0,000 < 0,05, a calculated t value of 5,968 > t table 1,984 and there is an effect of brand image on purchasing decisions with a significance value of 0,001 < 0,05, a calculated t value of 3,569 > t table 1,984. Meanwhile, the magnitude of the effect of these two variables obtained a significance value of 0,000 < 0,05 and f count 279,520 > f table 3,09, it is concluded that lifestyle and brand image together have an effect on purchasing decisions or it can be said that the hypothesis is a accepted